A semi-active suspension using a magnetorheological damper with nonlinear negative-stiffness component. (15th January 2021) - Yang, J.; Ning, D.; Sun, S.S.; Zheng, J.; Lu, H.; Nakano, M.; Zhang, S.; Du, H.; Li, W.H.
Highlights: A semi-active suspension which can produce a stroke-dependent actuating force is proposed. This suspension performs both high controllability and effective stiffness nonlinearity. The controllable damping force compensates the actuating force to further improve the control effect. A hybrid algorithm based on TS fuzzy and robust control considering the stiffness variation is implemented. Abstract: The group of active suspensions with controllable actuating force is noted with their excellent performance in reducing vibrations, however, their demanding requirements for high power consumption and high cost as well as the highly potential instability issue have hindered their practical usage. Semi-active suspensions with controllable stiffness or damping are simple, stable and cost-efficient, but they cannot provide equivalent performance with active suspensions. By incorporating the negative stiffness mechanism into the semi-active suspension using a magnetorheological (MR) damper, this paper provides a solution to improving the vibration-reduction performance of the semi-active suspensions to the level achievable by active suspensions while avoiding the disadvantages of active control. The experimental results demonstrated that the new suspension has brought better vibration-reduction performance than the passive suspension and the conventional MR suspension, and that the vibration reduction performance is comparable with that of some of the active systems reported. Therefore, this new semi-active suspension using MR damper with negative stiffness component can be considered as a new generation of vibration control method given that it has led to a great advancement in semi-active vibration control technology.